Curiosity - Blackwood, Gary L. (New York, New York : Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC, 2014)
In 1835, when his father's put in a Philadelphia debtor's prison, 12-year-old chess prodigy Rufus Goodspeed is relieved to be recruited to secretly operate a chess-playing automaton named The Turk, but soon questions the fate of his predecessors and his own safety.
Keywords: Chess -- Juvenile fiction; Apprentices -- Juvenile fiction; Poverty -- Juvenile fiction; Robots -- Juvenile fiction; d; Philadelphia (Pa.) -- History -- 19th century -- Juvenile fiction; Chess -- Fiction; Apprentices -- Fiction; Poverty -- Fiction; Robots -- Fiction; d; Philadelphia (Pa.) -- History -- 19th century -- Fiction; d; Apprentices; Chess; Poverty; Robots; Pennsylvania -- Philadelphia; 1800 - 1899; Fiction; Juvenile works